2021
DOI: 10.1021/acssuschemeng.1c02795
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Nanoparticles Dictate Their Toxicity by Regulating Adsorption of Humic Acid Molecules

Abstract: In an aquatic environment, nanoparticles (NPs) acquire coatings of natural organic matter (NOM) that alter the fate and toxicity of NPs. However, the essential relationship between engineered NP properties and NOM assemblage that determines how NPs are modified and behave at biological interfaces remains unclear. Herein, we use a complementary experimental and molecular dynamics approach to elucidate the mechanisms underlying adsorption of humic acid (HA) on NPs of different surface properties and effects on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 70 publications
1
13
1
Order By: Relevance
“…Dynamic light scattering showed an increase in the hydrodynamic size and zeta potential measurements of bare VAuNPs, compared to PC-VAuNPs ( Figures 1C,D ), and were recorded as 99.94 ± 3.41 and 226.14 ± 5.12, and -31.9 mV and +9.21 mV, respectively. Similarly to the increase in the nanoparticle size and surface charge reversal observed in our study, Li et al (2021) reported that humic acid adsorption on AuNPs increases their effective size and reverses nanoparticle surface charge. Further, Boldeiu et al (2019) reported that citrate- and honey-capped AuNPs suspended in culture media supplemented with 10% FBS resulted in the formation of PC around AuNPs, which promoted agglomeration and clustering of the AuNPs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Dynamic light scattering showed an increase in the hydrodynamic size and zeta potential measurements of bare VAuNPs, compared to PC-VAuNPs ( Figures 1C,D ), and were recorded as 99.94 ± 3.41 and 226.14 ± 5.12, and -31.9 mV and +9.21 mV, respectively. Similarly to the increase in the nanoparticle size and surface charge reversal observed in our study, Li et al (2021) reported that humic acid adsorption on AuNPs increases their effective size and reverses nanoparticle surface charge. Further, Boldeiu et al (2019) reported that citrate- and honey-capped AuNPs suspended in culture media supplemented with 10% FBS resulted in the formation of PC around AuNPs, which promoted agglomeration and clustering of the AuNPs.…”
Section: Resultssupporting
confidence: 87%
“…The ZnONPs with PC exhibited less cytotoxicity, chromosomal aberrations and micronuclei formation compared to ZnONPs without PC. Further, though not in plants, Li et al (2021) demonstrated that humic acid adsorption onto AuNPs increases their size and hydrophobicity and reverses the surface charge, which sterically hinders the binding of AuNPs to bacterial cell membrane. Thus, the toxicity of nanoparticles is mitigated by a decrease in the chance of AuNPs association with bacteria, and AuNPs-induced membrane damage.…”
Section: Resultsmentioning
confidence: 98%
“…Very recently, scientists reported that nanoparticle binding to the bacterial membrane depends on the natural organic matter adsorbed onto them in the aqueous medium. 50 Such type of adhesion dictates the nanomaterial to behave differently to other surfaces. So, this also may be influenced by the functional group or other characteristics of the molecules, as observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the interaction between HA-adsorbed MPs and cells may be suppressed by increased electrostatic repulsion (Wang et al, 2016). For example, Li et al (2021) found that the binding of gold nanoparticles (GNPs) to bacteria was suppressed by electrostatic repulsion between negatively charged groups in adsorbed HA and lipopolysaccharides on the bacterial membrane. Collectively, the adsorption of HA may result in less tight binding between MPs and the gill tissue, and consequently cause MPs to be easily removed from the fish gills during the depuration period.…”
Section: Accumulation Of Mps With Ha In Fish External Tissuesmentioning
confidence: 99%
“…Therefore, the accumulation of MPs in the fish gut may increase with increasing MP stability in water. Li et al (2021) reported that fish can display coughing behavior once the accumulation of MPs in the mouth exceeds a tolerance threshold. The adsorption of HA may reduce the coughing behavior of fish, decrease the clearance of MPs, and thus increase the number of MPs swallowed into the gut.…”
Section: Accumulation Of Mps With Ha In Fish External Tissuesmentioning
confidence: 99%